Physiological mechanisms of 2,4-epibrassinolide treatment in enhancing salt-alkali stress tolerance in Corylus heterophylla × C. avellana hybrid seedlings - MA Chao; CHEN Weiqing; LIU Zaiguo; HAO Jing; ZHAO Mengjiong; LU Juan (Guoshu xuebao)
[Objective] The present study was conducted to assess the impact of exogenous 2,4-epibrassionolide (EBR) on the growth and physiological responses of Corylus heterophylla × C. avellana hybrid seedlings under saline-alkali stress, with the objective of enhancing their tolerance to such adverse conditions. [Methods] The experiment was initiated with two-year-old seedlings from root suckers propagated by green branch layering with the hazelnut variety Dawei, widely cultivated in Xinjiang. These seedlings were transplanted into pots containing a mixture of garden soil, perlite, and humus in a ratio of 2∶1∶1. The seedlings were subjected to four treatments: (1) the control with normal cultivation (CK), (2) saline-alkali stress with a solution of 200 mmol·L-1 NaCl∶Na2CO3 in a ratio of 1∶1 (SA), (3) saline-alkali stress combined with 0.2 μmol·L-1 EBR (SE), and (4) saline-alkali stress combined with 0.2 μmol·L-1 EBR and 24 μmol·L-1 brassinazole (BRZ) (SEB). The seedlings were irrigated with the saline-alkali solution every three days for a total of three applications, and EBR or BRZ was applied every two days for five times. After 30 days of stress imposition, phenotypic observations were recorded, and samples were collected for subsequent analysis. [Results] The saline-alkali stress significantly inhibited the growth of the seedlings, but the application of 0.2 μmol·L-1 EBR notably mitigated this inhibitory effect. The EBR treatment led to a significant increase in the net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr) by 33.33% to 54.10% compared to the saline-alkali stress treatment alone. This enhancement in photosynthetic parameters suggested that EBR played a crucial role in maintaining the photosynthetic capacity under stress conditions, which was vital for the energy and carbon skeletons required for plant growth and survival. Furthermore, the EBR treatment significantly enhanced the content of chlorophyll a (Chl a), chlorophyll b (Chl b), and total chlorophyll (Chl a+b) by 37.05% to 41.38%. The increase in chlorophyll content indicated that EBR may protect the photosynthetic pigments from degradation, thereby preserving the light-harvesting capacity of the plant. Regarding physiological and biochemical indicators, the EBR treatment markedly increased the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), and significantly reduced the levels of hydrogen peroxide (H2O2) and superoxide anion generation rate (O2-) by 38.52% and 51.66%, respectively. These results indicated that EBR enhanced the plant's antioxidant defense system, which was crucial for scavenging reactive oxygen species (ROS) and preventing oxidative damage to cellular components. Additionally, EBR significantly promoted the accumulation of soluble sugars (SS), soluble proteins (SP), and proline (Pro) contents, increasing these parameters by 29.43% to 63.31% compared to the saline-alkali stress treatment. The accumulation of these osmoprotectants suggested that EBR helped the plant to maintain cellular hydration and protect against cellular dehydration under saline-alkali stress. In terms of ion balance, EBR treatment significantly decreased the sodium ion (Na+) content and the sodium-potassium ratio (Na+/K+) by 20.80% and 56.88%, respectively, while increasing the potassium ion (K+) content by 45.65%. These findings indicated that EBR played a role in modulating ion homeostasis, which was essential for maintaining cellular functions and reducing the toxic effects of sodium ions. In the context of organic acid metabolism, EBR treatment significantly increased the levels of succinic acid, citric acid, malic acid, and tartaric acid by 21.74%, 76.75%, 47.15%, and 63.77%, respectively. The increase in organic acid content suggested that EBR may enhance the plant's ability to cope with saline-alkali stress through various mechanisms, including osmotic adjustment, ion chelation, and detoxification. Regarding endogenous hormones, EBR treatment significantly reduced the abscisic acid (ABA) content by 20.58% and increased the content of indole-3-acetic acid (IAA), gibberellins (GA), and zeatin riboside (ZR) by 38.40%, 21.58%, and 21.14%, respectively. The modulation of hormone levels by EBR indicated its role in regulating plant growth and stress responses, which was crucial for plant adaptation to saline-alkali conditions. [Conclusion] The exogenous application of EBR significantly enhanced the tolerance of Corylus heterophylla × C. avellana hybrid seedlings to saline-alkali stress through multiple pathways, including the alleviation of oxidative damage, promotion of photosynthesis, enhancement of osmotic adjustment, maintenance of ion balance, regulation of organic acid metabolism, and modulation of endogenous hormone balance. These findings suggested that EBR could be a promising plant growth regulator for improving the productivity of hazelnut in saline-alkali soils, offering new insights and approaches into enhancing the yield and quality of crops in such challenging environments.